THE EFFECT OF TEAM GAMES TOURNAMENT ON STUDENTS’ READING COMPREHENSION ACHIEVEMENT - Phupuh Citra Dewi and Sri Minda Murni (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2015)
This study attempts to discover the effect of using Team Games Tournament Technique on students’ achievement in reading report text. It was conducted by using experimental research design. The population of this research was the eleventh (XI) grade students of SMA Hang Tuah Belawan which consists of 4 parallel classes with the total number of students is 120. The samples of this research were taken by random sampling through lottery technique. The result was class XI1 consisted of 30 students became the experimental group and class XI3 consisted of 30 students became the control group. The experimental group was taught by Team Games Tournament Technique while the control group was taught by using lecture technique. The instrument was used to collect the data was reading report text. After the data were analyzed, it was found that the value of t-test was 5,50 with the degree of freedom (df) = 58 at the level significance 0.05. it means that t-test was higher than t-table (5,50 > 2,000. Therefore, the null hypothesis (Ho) is rejected and the hypothesis alternative (Ha) is accepted.